No gods and precious few heroes : Twentieth-century Scotland - Harvie, Christopher T. (Edinburgh : Edinburgh University Press, 1998)
The fourth edition of this classic text on the history of Scotland since World War I. Epitomised by political, social and technological change this history appraises a fast-evolving century, from the outbreak of World War I up to the present and the politics of devolution and the age of the internet. The book begins with the devastating impact of World War I and Scotland's critical role in its conduct, then continues to explore Scots institutional life, from 1922 to 1964, governed by the problems of economy, society, politics and culture embedded in a mature industrialised state with economic problems and governmental deficits. Two further chapters cover the period from 1964 to 1999, including the challenge of new industries, oil discoveries, and the rise of devolutionary and nationalist politics. A new section for this edition covers the course of devolved politics, from the Scottish parliament of 1999 to the financial collapse of 2008 and the constitutional upheavals of 2014-15, rounding off this unique interpretation of a century of Scottish life from a cherished and multi-faceted historian.
Introduction -- Introduction to the Edinburgh edition -- Acknowledgements -- 1. 'When the lamps went out' 1911-1922 -- 2. A troubled economy 1922-1964 -- 3. The pillars of society 1922-1964 -- 4. Politics and government 1922-1964 -- 5. Mass media: High culture 1922-1964 -- 6. Future deferred? Scotland 1964-1979 -- 7. The start of a new song? 1979-1997 -- Further reading -- Appendix: Chronological table 1906-2000 -- Index.
Series numbering from series title page of v. 7.
Includes bibliographical references (pages 185-190) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Scotland -- History -- 20th century; Écosse -- Histoire -- 20e siècle.; HISTORY; Scotland; 1900-1999; History